Nominalisation of phrasal verbs in the -ing forms with a plural marker (goings-on, coming outs): a study of nominal characteristics - Marie Turlais (Lexis: Journal in English Lexicology)
This article studies the formation and meaning of deverbal phrasal nouns such as goings-on or coming outs in relation to the prototypical characteristics of the nominal category. I will study the morphological, syntactic and semantic aspects of pluralised -ing nominalisations of phrasal verbs to show that this derivation process creates prototypical nouns. These constructions bear some resemblance to compound nouns, and are sometimes treated as such in the literature, but they are actually unprototypical compounds at best. Finally, two types of variation can be observed in the data: the location of the plural marker -s, which can fall either on the lexical base or on the right-hand particle, suggests two possible interpretations of the whole constituent, while the existence of competing nominalisations that do not feature the -ing suffix (a weighing-in // a weigh-in) indicates that the suffix triggers eventive readings of the nouns.